β3-Adrenoceptor as a new player in the sympathetic regulation of the renal acid–base homeostasis - Milano, Serena; Saponara, Ilenia; Gerbino, Andrea; Lapi, Dominga; Lela, Ludovica; Carmosino, Monica; Dal Monte, Massimo; Bagnoli, Paola; Svelto, Maria; Procino, Giuseppe (Frontiers in Physiology, 2024)
Efferent sympathetic nerve fibers regulate several renal functions activating norepinephrine receptors on tubular epithelial cells. Of the beta-adrenoceptors (β-ARs), we previously demonstrated the renal expression of β3-AR in the thick ascending limb (TAL), the distal convoluted tubule (DCT), and the collecting duct (CD), where it participates in salt and water reabsorption. Here, for the first time, we reported β3-AR expression in the CD intercalated cells (ICCs), where it regulates acid–base homeostasis. Co-localization of β3-AR with either proton pump H+-ATPase or Cl−/HCO3− exchanger pendrin revealed β3-AR expression in type A, type B, non-A, and non-B ICCs in the mouse kidney. We aimed to unveil the possible regulatory role of β3-AR in renal acid–base homeostasis, in particular in modulating the expression, subcellular localization, and activity of the renal H+-ATPase, a key player in this process. The abundance of H+-ATPase was significantly decreased in the kidneys of β3-AR−/− compared with those of β3-AR+/+ mice. In particular, H+-ATPase reduction was observed not only in the CD but also in the TAL and DCT, which contribute to acid–base transport in the kidney. Interestingly, we found that in in vivo, the absence of β3-AR reduced the kidneys’ ability to excrete excess proton in the urine during an acid challenge. Using ex vivo stimulation of mouse kidney slices, we proved that the β3-AR activation promoted H+-ATPase apical expression in the epithelial cells of β3-AR-expressing nephron segments, and this was prevented by β3-AR antagonism or PKA inhibition. Moreover, we assessed the effect of β3-AR stimulation on H+-ATPase activity by measuring the intracellular pH recovery after an acid load in β3-AR-expressing mouse renal cells. Importantly, β3-AR agonism induced a 2.5-fold increase in H+-ATPase activity, and this effect was effectively prevented by β3-AR antagonism or by inhibiting either H+-ATPase or PKA. Of note, in urine samples from patients treated with a β3-AR agonist, we found that β3-AR stimulation increased the urinary excretion of H+-ATPase, likely indicating its apical accumulation in tubular cells. These findings demonstrate that β3-AR activity positively regulates the expression, plasma membrane localization, and activity of H+-ATPase, elucidating a novel physiological role of β3-AR in the sympathetic control of renal acid–base homeostasis.